Analysis of the determinants of tax revenue in 5 ASEAN countries - Anggi Somba Poddala; Paulus Uppun; Hamrullah Hamrullah (AKUNTABEL: Jurnal Ekonomi dan Keuangan, 2023)
The number of taxpayers from year to year is increasing. However, it is not balanced with taxpayer compliance in paying taxes so that it becomes an obstacle in tax revenue. This study examines the level of tax revenue in five ASEAN countries including Indonesia, Malaysia, the Philippines, Singapore and Thailand. Researchers used panel data from 2006-2020 in 5 ASEAN countries. The model used is panel data regression using path analysis techniques. As for the results of the study show that investment directly has a significant effect on tax revenues. But indirectly, it has no significant effect on tax revenues through GDP. Meanwhile, government expenditure has a significant effect directly or indirectly through GDP on tax revenues.